Factors Influencing Health Social Media Use Habits Behavior among Older Adults in a Thai Provincial Setting: A Cross-Sectional Study - Somporn, Kanokporn; Srinathom, Chotika; Keawkhiew, Sasikan; Varakitsathaporn, Kanokwan; Phranphithak, Adithep; Singsu, Sittichai (National Journal of Community Medicine, 2026)
Background: As Thailand rapidly transitions into a fully aged society, understanding digital health communication channels is critical. Despite social media's potential for promoting older adults' self-care, the digital divide remains a significant barrier. This study examined factors influencing health social media use habits behavior among older adults in a Thai Provincial setting to inform targeted health interventions. Methods: A cross-sectional study design was employed, involving 402 community-dwelling older adults in Samut Songkhram Province, Thailand. Data were analyzed using descriptive statistics to summarize participant characteristics and stepwise multiple regression analysis to identify significant predictors of social media usage behavior. Results: Participants demonstrated a high level of social media usage (M=2.58, SD=0.55). Stepwise regression identified highest education level, age, chronic conditions, gender, and monthly income as significant predictors (p<0.05), collectively explaining 19.65% of the variance in social media use behavior. Conclusion: Socioeconomic and health-related factors significantly shape social media engagement among Thai older adults. These findings underscore the need for tailored digital health strategies that account for highest education level, age, chronic disease, gender, and average monthly income. Addressing these determinants can help bridge the digital divide, enhance access to quality health information, and ultimately support healthy aging in resource-limited settings.